Religion and spirituality - Dowson, Martin; Devenish, Stuart (International advances in education., 2010)
Religion and spirituality make critical contributions to an inclusive vision for the welfare of minorities, the marginalized and other disadvantaged groups in societies and cultures around the globe. Religious movements and spiritual traditions work to improve social outcomes for disenfranchised groups by enriching educational, political, and social agendas, and by providing a wide variety of justice-driven programs and services. Values underpinning these services include the dignity of the human person, the sanctity of human life, the foundational role of families and communities, the transformative power of learning, and the advancement of shared personal and social rights and responsibilities. These values act as a counter-balance to other attitudes and values that may impede pro-social cohesion and development.Drawing on diverse religious and spiritual perspectives and traditions, this new volume provides exciting and enriching examples of theory, research and practice that directly contribute to our understanding of how religion and spirituality promote and facilitate social justice and equity in diverse social and cultural contexts - with a particular focus on educational settings, contexts, processes and outcomes.Religious communities invest heavily in schools, colleges and universities in the belief that these educational institutions enable them to inculcate into their membership the kinds of moral values and qualities that lie at the heart of their spiritual teachings. Looking beyond the sacred-secular impasse, religious organisations attempt to provide a "education for life" which draws from both the scientia of science and the sapientia of religion and spirituality. These depth-dimensions provide the pool of values which enable citizens to enact equity, mercy and justice in society in the name of God and for the sake of humanity. The chapters which comprise this volume demonstrate the possibility of a healthy integration between religion and education from a truly global, transdisciplinary and ecumenical perspective. From contexts within Asia, Africa, the USA and Australia, and from disciplines ranging from ethics to social work, from health to educational curriculum, from personal identity to community-consciousness; this volume makes a unique contribution to the theory and practice of the educational and religious inter-face. It is a contribution which holds a great deal of promise for being pro-humanitas.